WOMEN’S LEADERSHIP AND MOTHERHOOD IN HIGHER EDUCATION: A CASE STUDY OF WOMEN ADMINISTRATORS IN A REGIONAL UNIVERSITY IN EAST KAZAKHSTAN - Abdulla, Nessibeli (Nazarbayev University Graduate School of Education, 2024)
This research explores the experiences of mothers who hold administrative positions in a regional university in East Kazakhstan. The study examines the challenges and benefits of balancing motherhood and administrative duties in higher education, aiming to inform the development of supportive structures for these women. This study used a qualitative method with semi-structured interviews as the data collection instrument. It delves into the challenges these mother administrators face, including work-life conflicts, workplace dynamics, and access to institutional support. The study also identifies positive aspects of having the dual role, including personal fulfillment, career advancement, and contributions to diversity within the institution. The findings highlight the significance of implementing flexible work schedules, providing leadership training and coping strategies to support female administrators. These measures can contribute to increasing job satisfaction, improving retention rates, and fostering a more inclusive and supportive work environment. This study adds to the existing body of knowledge on female leadership in higher education by providing practical insights for educational institutions to enhance their support systems for female administrators.
Keywords: Type of access: Open Access; motherhood; administrative positions